ANALISIS PENGARUH PENEMPATAN KARYAWAN, KARAKTERISTIK INDIVIDU, DAN STRES KERJA TERHADAP KINERJA (Survei pada Karyawan Non PNS RSUD Dr. Harjono S Kabupaten Ponorogo) - Ariani, Ririn; Suseno, Y. Djoko; Sutarno, Sutarno (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
Organizational performance is largely determined by the performance of human resources that contribute to it. The high work performance of employees is the achievement achieved by the employee at a certain level. Employee performance is not just a coincidence, but many factors influence it. Several factors affect employee performance, namely employee placement, individual characteristics, and work stress. The purpose of this study was to determine the effect of employee placement, individual characteristics, and work stress on performance of Non Civil Servant Employees at The Regional General Hospital (RSUD) Dr. Harjono S Ponorogo Regency. Data collection in the form of answers to the questionnaire as primary data and documentation as secondary data. The number of research samples as many as 80 employees with a sampling method using random sampling. Data analysis methods used are validity and reliability test, classic assumption test, hypothesis test, F test, and coefficient of determination test. The results of multiple linear regression calculations using the t test showed that the placement of employees and individual characteristics significantly influence the performance of Non Civil Servant Hospital Dr. Harjono S Ponorogo Regency. This is indicated by the significant probability value of each variable < 0.05. While work stress does not have a significant effect on the performance of Non Civil Servants Hospital Dr. Harjono S Regency Ponorogo. This is indicated by the significant probability value > 0.05.